Pengaruh Harga Bensin terhadap Kecelakaan Lalu Lintas di Indonesia - Kusdarwati, Eny; Hartono, Djoni (Jurnal Ekonomi dan Pembangunan Indonesia, 2016)
Traffic accident ranks the ninth largest of the cause of death in Indonesia. The most of researches studying Indonesia on traffic accidents were only blaming on human, motor vehicles, and environment as main culprits, not incorporating economic factors into the models. This study aims to analyze the impact of real gasoline prices on traffic accident in Indonesia and the factors of influence them. This research employs time series data from 1970 to 2013 with OLS analysis world crude oil prices as instrument variable. The estimator results show that real price of gasoline and the policy of usage of motorcycle light insignificant on traffic accident. Meanwhile, real GDP and asphalt roads significantly decrease the traffic accident. However, motorcycles significantly increase the traffic accident.